2012
DOI: 10.1111/j.1476-4431.2012.00799.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of intra‐abdominal pressure in dogs and cats

Abstract: Further studies investigating IAP in critically ill veterinary patients are required to establish the optimal technique for this measurement in veterinary medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(58 citation statements)
references
References 105 publications
1
54
1
2
Order By: Relevance
“…Earlier intervention in states of perioperative pain, hypothermia, hypovolemia, and hypoxemia may lead to improved tissue oxygenation and a lower incidence of SSI . In a study of 59 postoperative patients, those who did not develop an SSI had higher StO 2 levels 12 hours after surgery than those who developed an SSI . The low StO 2 values and subsequent SSI in some postoperative patients may also be a result of vasoconstriction and decreased oxygen delivery to the tissues.…”
Section: Human Literature Reviewmentioning
confidence: 46%
See 1 more Smart Citation
“…Earlier intervention in states of perioperative pain, hypothermia, hypovolemia, and hypoxemia may lead to improved tissue oxygenation and a lower incidence of SSI . In a study of 59 postoperative patients, those who did not develop an SSI had higher StO 2 levels 12 hours after surgery than those who developed an SSI . The low StO 2 values and subsequent SSI in some postoperative patients may also be a result of vasoconstriction and decreased oxygen delivery to the tissues.…”
Section: Human Literature Reviewmentioning
confidence: 46%
“…There is a direct relationship between the magnitude of oxygen deficit and the risk of multiorgan failure, which has lead to a treatment rationale that optimizes cardiac output and hematocrit to correct deficits in VO 2 and tissue oxygen delivery . Smith et al showed that StO 2 values predicted the need for early pRBC transfusions in trauma patients showed that StO 2 values were lower in human patients that had received aged (>21 days) pRBC transfusions, although Creteur et al found no correlation between the age of pRBC and StO 2 following transfusion .…”
Section: Human Literature Reviewmentioning
confidence: 99%
“…Il existe de nombreuses méthodes pour mesurer la PIA [1,4]. Il est possible d'utiliser une sonde vaginale ou rectale [5].…”
Section: Mesure De La Pression Intra-abdominaleunclassified
“…The increased pressure within the abdominal cavity can adversely affect normal perfusion and function in the surrounding tissues, and eventually this process can lead to physiologic dysfunction and multiple organ failure . In veterinary medicine, there have been a few reports of IAH and ACS having multiple negative systemic effects . Awareness of IAP in veterinary patients with critical abdominal disease is essential for optimal patient management …”
Section: Introductionmentioning
confidence: 99%